Migration, Knowledge Transfer, and the Emergence of Australian Post-War Skiing: The Story of Charles William Anton. Issue 16 (1st November 2016) - Strobl, Philipp
Abstract: Skiing underwent substantial changes during the post-war years when the sport turned into a multi-billion dollar industry and a leisure activity for the masses. Despite its global nature and popularity, skiing in academic writing has not gained much recognition. This paper explores the role of knowledge transfer during the pioneering phase of post-war skiing in Australia. It describes the life of Charles William Anton, an Austrian refugee from the Anschluss who migrated to Sydney and subsequently became one of the founding fathers of Australian post-war skiing. The following pages show the multi-layered nature of skiing as a global sport by exemplifying how ideas spread from pre-war Europe to post-war Australia. The paper will also provide a case study about refugee knowledge transfer and the 'productive process of absorption, adoption or rejection of knowledge' that takes place once an idea has been introduced into a new environment.